Low & Anaplastic Grade Glioma Umbrella Study of MOlecular Guided TherapieS (LUMOS-2): study protocol for a phase 2, prospective, multicentre, open-label, multiarm, biomarker-directed, signal-seeking, umbrella, clinical trial for recurrent IDH mutant, grade 2/3 glioma - Marshall Pitz; Eng-Siew Koh; Elizabeth H Barnes; Lucille Sebastian; Mandy L Ballinger; David M Thomas; Christopher O'Callaghan; John Simes; Hui K Gan; Sonia Yip; Hao-Wen Sim; Desma Spyridopoulos; et al. (BMJ Open)
Introduction All grade 2/3 gliomas are incurable and at the time of inevitable relapse, patients have significant unmet needs with few effective treatments. This study aims to improve outcomes by molecular profiling of patients at relapse, then matching them with the best available drug based on their molecular profile, maximising the chances of patient benefit while simultaneously testing multiple novel drugs.Methods and analysis Low & Anaplastic Grade Glioma Umbrella Study of MOlecular Guided TherapieS (LUMOS-2) will be an international, phase 2, multicentre, open-label, biomarker-directed, umbrella clinical trial for recurrent isocitrate dehydrogenase mutant, histologically grade 2/3 gliomas. Investigational treatment will be assigned based on molecular profiling of contemporaneous tissue obtained at disease relapse using next-generation sequencing. LUMOS-2 will begin with three therapeutic treatment arms: paxalisib, cadonilimab and selinexor. Patient molecular profiles will be assessed by an expert, multidisciplinary Molecular Tumour Advisory Panel. Patients whose molecular profile is considered suitable for a targeted agent like paxalisib will be allocated to that arm, others will be randomised to the available arms of the trial. The primary endpoint is progression-free survival at 6 months. Secondary objectives include assessment of overall survival, response rate, safety and quality of life measures. Two additional therapeutic arms are currently in development.Ethics and dissemination Central ethics approval was obtained from the Sydney Local Health District Ethics Review Committee, Royal Prince Alfred Hospital Zone, Sydney, Australia (Approval: 2022/ETH02230). Other clinical sites will provide oversight through local governance processes, including obtaining informed consent from suitable participants. A report describing the results of the study will be submitted to international meetings and peer-reviewed journals.Trial registration number ACTRN12623000096651.